Fine Needle Aspiration Cytology Findings of Breast Lesions in Western Region of Nepal - Ghimire, Pragya Gautam; Ghimire, Prasanna; Gupta, Sharmila (Journal of Nepalgunj Medical College, 2018)
Aim: Breast cancer is the most common neoplasm worldwide. Fine needle aspiration cytology is a minimally invasive, highly sensitive and cost effective investigation for breast lesions. The aim of our study was to evaluate the spectrum of fine needle aspiration cytology findings of breast lesions. Material and Methods: It was a prospective study conducted in the Department of Pathology during a 2 year period from Jun 2016- May 2018. A total of 284 patients with breast lesions were subjected to ultrasound guided fine needle aspiration cytology. Result: The age of presentation ranged from 13 years to 81 years with a mean age of 34.9±13.5 years. Most common age group for breast lesions was in 21-30 age groups (39.1%). Fibro adenoma was the most common benign pathology (26.8%) followed by fibrocystic changes (26.4%). Malignancy was noted in 16.2% with majority in the 41-50 age groups. Parasitic infection was noted in 2 cases. Conclusion: Screening of breast lesions is warranted resulting in significant reduction of morbidity and mortality related to breast cancers. Fine needle cytology plays a pivotal role in the overall management of breast lesions.